Evaluation of Bond Strength of Denture Base Resin to a Cross-Linked Denture Teeth with Various Auxiliary Retentive Features: An In Vitro Study - Kumari, Pushpa; Arunachalam, Sudheer; Mondal, Susmita; Priya, Priya (Journal of Neonatal Surgery, 2025)
Background: This study was conducted to assess the Bond Strength of Denture Base Resin to a Cross-Linked Denture Teeth with Various Auxiliary Retentive Features. Material and methods: The study was conducted in the Department of Prosthodontics and Crown and Bridge of Mithila Minority Dental College and Hospital, Darbhanga, Bihar. The objective of this study was to compare the bond strength of cross-linked denture teeth to Lucitone199 heat cure denture base resin after various mechanical modification of the bonding surface area of cross-linked denture tooth. 80 left maxillary cross-linked acrylic central incisor denture teeth (Cosmo HXLTM Acrylic two layered teeth, DENTSPLY Dental (Tianjin) Co., Ltd, China) of same size and shade were selected. The 80 teeth were then divided into 4 Groups. The 4 Groups were named Group 1, 2, 3 and 4 according to the mechanical modification of the surface treatments in which group 1 served as control group with no surface mechanical modification. Group 2, round groove Group3, vertical groove and Group4T-shaped groove. Wax models were made using a custom-made jig such that the tooth was placed with a labial inclination of 1300 from the denture base. The wax models were invested. Results: When comparing the other Groups with the control Group, there is a statistical difference between the mean bond strength values of vertical groove and T-Shaped groove.The mean bond strength values of vertical groove and T-Shaped groove (646.65N and 721.43N) were significantly higher (p<0.05) than that of the control Group (510.29N) as proved from Tukey’s HSD test.Round groove (519.32N) had no statistically (p>0.05) significant mean bond strength values when compared to the control Group (510.29N).When compared to the vertical groove and T- Shaped groove (646.65N and 721.43N), had statistically highest (p<0.05) mean bond strength value of 721.43N and was proved statistically with Tukey’s HSD test. Conclusion: The mechanical modification on the bonding surface of acrylic teeth before packing definitely improved bonds strength. The T-Shaped group had the highest mean bond strength values and all the failures were cohesive in nature. Vertical groove group had good bond strength values but more of adhesive failure was noted. There was no statistical difference in mean bond strength values of control, round groove groups. Adhesive failures were seen in the Vertical groove and control groups. T-Shaped had good bond strengths leading only to cohesive failure.